The Influence of Good Corporate Governance, Political Visibility And Profitability To Corporate Social Responsibility Disclosure (CSR) On Manufacturing Companies Listed In BEI - Enika Diana Batubara; Syaharman; M. Nursidin; Yenni Ramadhani Harahap (CERED Indonesia Institute, 2022)
The issue of disclosure of social responsibility is growing rapidly. Research on social responsibility disclosure results in different findings. The purpose of this study is to explain the effect of the size of the board of commissioners, the proportion of the board of commissioners, the audit committee, the size of the company (size), the type of company and profitability as independent variables on the disclosure of social responsibility (CSR) as the dependent variable. The sample in this research is a company listed on the Stock Exchange Indonesia in 2015 which annual report contains the activities of corporate social responsibility and can be accessed through the website of BEI, which is a number of 50 companies by using purposive sampling techniques. The analysis technique used is descriptive analysis and statistical analysis. The test results show that simultaneously the size of board of commissioners, composition of board of commissioners, audit committee, firm size, industry type and profitability have significant effect, because under significant level <0,05 to disclosure corporate social responsibility. This means that the size of the board of commissioners, the composition of the board of commissioners, audit committee, firm size, industry type and profitability can affect the level of social disclosure activities in a company. The results of the test show that in a significantly different manner the size of the Board of Commissioners (0,000 <0.05), Proportion of Independent Commissioners (0.000 <0.05), Independent Audit Committee (0.002 <0.05), and Size (0.003) <(0.05), Industrial Type (0.023) <(0.05), which means that the size of the Board of Commissioners, the Proportion of Independent Commissioners, the Independent Audit Committee, the Company Size, Industrial Type and Profitability partially influence the disclosure of Corporate Social Responsibility and able to influence the level of Corporate Social Responsibility disclosure activities on the company.